A general hypothesis of forest invasions by woody plants based on whole‐plant carbon economics. (19th October 2022) - Fridley, Jason D.; Bellingham, Peter J.; Closset‐Kopp, Déborah; Daehler, Curtis C.; Dechoum, Michele S.; Martin, Patrick H.; Murphy, Helen T.; Rojas‐Sandoval, Julissa; Tng, David
Abstract: Although closed‐canopy forests are characterized by low‐light availability and slow population dynamics, many are under threat from non‐native, invasive woody species that combine high colonization ability and fast growth potential with high low‐light survival. This 'superinvader' phenotype contravenes expected trade‐offs predicted by successional niche theory, posing a challenge to both invasion and forest succession theory. We propose a parsimonious conceptual model based on the whole‐plant light compensation point (WPLCP) that, across a variety of plant strategies and growth forms, can explain greater competitive abilities of forest invaders in the context of both high‐light growth rate and shade tolerance. The model requires only that non‐native species experience relatively fewer carbon costs than native species, enabling resource‐acquisitive species to establish in low‐light conditions. We review evidence for lower carbon costs in invasive species resulting from (1) enemy release, (2) recent environmental changes that favour less stress‐tolerant phenotypes and (3) phylogenetically constrained native floras. We also discuss implications of invader shade tolerance in the context of other life‐history strategies that, combined with canopy disturbances, facilitate their rapid numerical dominance. Synthesis . An invasion framework driven by carbon dynamics suggests renewed focus on whole‐plant carbon costs, including below‐ground respiration and tissue turnover, which are rarely measured in functional studies of forest invaders. Abstract : An invasion framework driven by carbon dynamics suggests renewed focus on whole‐plant carbon costs, including below‐ground respiration and tissue turnover, which are rarely measured in functional studies of forest invaders.